Youth and Social Capital in Bosnia and Herzegovina - Kovačević, Biljana; Sijakovic, Ivan; Petrovic, Jagoda (Italian Sociological Review, 2019)
This paper examines levels of social trust and its influence on the development of social capital among young people in Bosnia and Herzegovina. In the first part of the paper, we give an initial theoretical overview that serves as a framework for the survey. The aim of the paper is to investigate different types of social capital and to review the extent in which the social trust enables efficient building of social networks, connections and ties. In the second part of the paper, we present our survey, conducted in the year 2017. The case of a 1,352 people from 15 to 30 years of age. The survey is showing a general lack of trust among young people in Bosnia and Herzegovina and its negative impact on society’s development.